Biological mechanisms of pulmonary inflammation and its association with seropositive rheumatoid arthritis - Yang, Peiyue; Song, Yuqing; Li, Mingwei (Frontiers in Immunology, 2025)
Although the pathogenesis of seropositive rheumatoid arthritis (RA) remains unclear, studies suggest that pulmonary inflammation-related biological mechanisms play a significant role in its development. This review thoroughly explores the mechanisms underlying early pulmonary lesions in seropositive RA, focusing on the mucosal barrier hypothesis, neutrophil extracellular traps, pathogenic microbial infections like COVID-19, Vitamin D, the microbiome and gut-lung axis, inhalation exposures and chronic pulmonary diseases. This study seeks to provide novel insights and theoretical foundations for the prevention and treatment of seropositive rheumatoid arthritis.